Advanced Frequency Reconfigurable Microstrip Antenna Based on Fractal Geometry for X-Band Applications - Rakesh Kumar Singh,; Surya Bhushan Dubey,; Kamal Prakash Pandey,; Saiyed Salim Sayeed,; Amrees Pandey, (Utilitas Mathematica, 2025)
This work presents the design and analysis of a frequency reconfigurable microstrip patch antenna based on fractal geometry for X-band satellite communication. The antenna operates in two switching configurations controlled by a single PIN diode modeled in HFSS. In the OFF state, the antenna covers 8.81–9.65 GHz and 10.28–12.61 GHz, with resonance frequencies at 9.23 GHz, 10.71 GHz, and 11.97 GHz, achieving peak gains of 9.23 dBi, 7.44 dBi, and 11.27 dBi, respectively. In the ON state, the operating bands shift to 8.81–9.44 GHz and 10.07–12.18 GHz, with resonances at 9.23 GHz, 10.71 GHz, and 11.34 GHz, providing peak gains of 6.64 dBi, 10.47 dBi, and 12.23 dBi. The simulated radiation efficiency is 71.19%, 75.63%, and 80.41% in the OFF state, and 72.01%, 78.34%, and 89.68% in the ON state. The inclusion of circular fractal slots in the ground plane significantly enhances bandwidth and gain performance. The findings demonstrate that the proposed fractal reconfigurable antenna offers high radiation efficiency and reliable multi-band operation, making it a strong candidate for X-band wireless and satellite communication applications.